ВПЛИВ МОНОКЛОНАЛЬНИХ АНТИТІЛ ДО TSLPR НА ЖИТТЄЗДАТНІСТЬ КЛІТИН MCF-7 ТА A549, ЕКСПРЕСІЮ В НИХ ПРОАПОПТОТИЧНИХ ГЕНІВ ТА ПРОДУКЦІЮ ПРОЗАПАЛЬНИХ ЦИТОКІНІВ - Rakha, Alyaa; Talaat, Roba M.; El-maadawy, Eman A.; Gurguis, Adel A. (PH Akademperiodyka, 2023)
Background. Thymic stromal lymphopoietin (TSLP) and its receptor (TSLPR) are expressed in various cancer cells. However, their role in cancer development is not well defined. Aim. To investigate the effects of anti-TSLPR antibody on the viability, proapoptotic genes expression, and production of pro-inflammatory cytokines in MCF-7 and A549 cancer cells. Materials and Methods. MCF-7 and A549 cells were exposed to anti-TSLPR monoclonal antibody for 24, 48, and 72 h. The effect on cell viability was examined by MTT assay. The expression levels of TP53, BAX, and CASP3 genes were evaluated by the quantitative reverse transcription polymerase chain reaction (qRT-PCR). Levels of interleukin (IL)-6, tumor necrosis factor-alpha (TNF-α), and transforming growth factor (TGF-β1) were measured by the enzyme-linked immunosorbent assay (ELISA). Results. The treatment of MCF-7 cells with anti- TSLPR antibody slightly stimulates cell proliferation after 48 h and 72 h following initial cytotoxicity in 24 h with a significant reduction in IL-6 and TNF-α production. A significant increase in the BAX expression in anti-TSLPR treated cells at a concentration of 2.5 μg/ml at 24-h point was evident. In anti-TSLPR-treated A549 cells, no decrease in cell count was observed, and slight dose-dependent stimulation of cell proliferation was evident in 48 h and 72 h of culture. A significant increase in TP53, BAX, and CASP3 expression upon treatment with 2.5 μg/ml of anti-TSLPR was evident in A549 cells. Conclusion. The effects of anti-TSLPR on cell viability, proapoptotic gene expression, and production of pro-inflammatory cytokines (IL-6 and TNF-α) vary in MCF-7 and A549 cells.